Disabled people's experiences of accessing reasonable adjustments in hospitals: a qualitative study - Stuart Read; Pauline Heslop; Sue Turner; Victoria Mason-Angelow; Nadine Tilbury; Caroline Miles; Chris Hatton (BMC, 2018)
Abstract Background The UK Equality Act 2010 requires providers of health services to make changes or 'reasonable adjustments' to their practices in order to protect disabled people from discrimination or disadvantage when accessing care. Existing evidence suggests that despite this legislation, health services are not always providing reasonably adjusted care for disabled people. This paper presents the perspectives of disabled people themselves in relation to their experiences of accessing reasonable adjustments in hospitals in England. Methods Twenty-one semi-structured interviews were held with disabled people who had a recent experience of hospital care in England. Participants were asked about the extent to which the hospital provided reasonably adjusted care, and if necessary, how they thought the provision of reasonable adjustments could be improved. Each interview was anonymised and transcribed, and the data analysed using thematic analysis. Results Participants reported mixed experiences about whether and how reasonable adjustments were provided: some shared positive examples of good practice; others spoke about difficult encounters and limited provision. Recommendations made include a need for culture change in how reasonable adjustments are perceived and enacted; improvements in identifying the needs of disabled people; improvements to the hospital environment and the provision of information; and the need to involve disabled people themselves in the process of change. Conclusions Gaps remain in how reasonable adjustments are provided for disabled people accessing hospital care. It is important for hospital staff to listen to the perspectives of disabled people about the provision of reasonable adjustments, and make improvements as necessary. Hospital staff could also do more to share good practice in relation to the provision of reasonable adjustments to effectively inspire and embed positive change.